2005
DOI: 10.1530/rep.1.00761
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in bovine cumulus–oocyte complexes after exposure to polychlorinated biphenyl mixtures during in vitro maturation

Abstract: Aroclor-1254 (A-1254) is a commercial mixture of coplanar (dioxin-like) and non-coplanar (non dioxin-like) polychlorinated biphenyls (PCBs) affecting bovine oocyte in vitro maturation (IVM) and developmental competence. In the present study, the role of cumulus cell apoptosis in mediating the toxic effects of PCBs during in vitro maturation has been investigated. Results indicate that exposure of cumulus -oocyte complexes (COCs) to A-1254 significantly induced apoptosis of cumulus cells. Furthermore, A-1254 si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…Furthermore, we observed that in the presence of bNF a significant increase in cumulus cells apoptosis occurs only in the absence of follicular fluid, whereas no difference was observed in the presence of the latter compared with control, indicating that apoptosis may be at the basis of the ovotoxicity observed. These data are in agreement with previous results in bovine COCs, indicating that PCB 126, another potent AhR-ligand, induces apoptosis in cumulus cell mass (Pocar et al 2005). Several studies implicate the AhR as having a role in modulating or mediating apoptotic processes.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we observed that in the presence of bNF a significant increase in cumulus cells apoptosis occurs only in the absence of follicular fluid, whereas no difference was observed in the presence of the latter compared with control, indicating that apoptosis may be at the basis of the ovotoxicity observed. These data are in agreement with previous results in bovine COCs, indicating that PCB 126, another potent AhR-ligand, induces apoptosis in cumulus cell mass (Pocar et al 2005). Several studies implicate the AhR as having a role in modulating or mediating apoptotic processes.…”
Section: Discussionsupporting
confidence: 93%
“…Signaling molecules in the regulation of the apoptosis are distributed among cells in the COCs [22]. One key signaling cascade regulated by FSH-FSHR interaction is the production of second messenger molecules (cAMP) and IP3.…”
Section: Discussionmentioning
confidence: 99%
“…Aroclor 1254 inhibited in the vitro maturation and development competence of bovine oocytes [22] as well as inducing cumulus cell apoptosis [23]. Furthermore, adverse effects of exposure to Aroclor 1254 during oocyte maturation were extended to fertilization and embryonic development [8].…”
Section: Discussionmentioning
confidence: 99%